2023
DOI: 10.1177/10711007231176512
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Failure of Total Ankle Replacements: A Data Linkage Study Using the National Joint Registry and NHS Digital

Abstract: Background: Despite the increasing numbers of ankle replacements, there remains debate about which patients should undergo an ankle replacement, and there are limited studies analyzing risk factors for failure of an ankle replacement. The primary aim of this study is to analyze the risk factors for failure of total ankle replacements. Methods: A data linkage study combining the National Joint Registry (NJR) Data and NHS (National Health Service) Digital data was performed. The primary outcome of failure is def… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 63 publications
0
9
0
Order By: Relevance
“…They reported that lower age, increased BMI, and indication for surgery have a significantly increased risk of TAR failure. 8 The literature has been largely consistent on this topic. Most studies have reported similar levels of complications, infection, and failure regardless of BMI.…”
mentioning
confidence: 95%
See 4 more Smart Citations
“…They reported that lower age, increased BMI, and indication for surgery have a significantly increased risk of TAR failure. 8 The literature has been largely consistent on this topic. Most studies have reported similar levels of complications, infection, and failure regardless of BMI.…”
mentioning
confidence: 95%
“…In this issue of FAI, 2 articles provide important insights into the effect of body mass index (BMI) on TAR outcomes. 8,9 Kim et al 9 evaluated the effect of obesity on complication rates and patient-reported outcome (PRO) measure scores in a single-institution, retrospective comparative study of 1093 primary TARs. They found that obese patients did not experience increased rates of complication, revision, or infection after TAR.…”
mentioning
confidence: 99%
See 3 more Smart Citations